Serum creatinine, genetic susceptibility, and the risk of osteoporosis and fracture: a prospective cohort study from the UK Biobank - He, Weijie; Zhou, Yu; Ding, Jiaxuan; Jiang, Jiale; Zhang, Hang; Hu, Chonghui; Liu, Qiongyan; Gu, Honglin; Chen, Huimou (Frontiers in Endocrinology, 2026)
BackgroundOsteoporosis imposes a substantial fracture burden, yet scalable and dynamic biomarkers for risk stratification remain limited. Serum creatinine—routinely assayed and capturing intertwined muscle and renal signals—has been little studied for incident osteoporosis or fractures.MethodsIn the UK Biobank, covariate-adjusted Cox models and restricted cubic splines assessed associations of baseline creatinine with incident osteoporosis and fractures. Creatinine was modeled categorically (six strata; G4 [70–80 μmol/L] as reference) and continuously. The pre-defined analysis was stratified by sex and age (>65) as well as the three tertiles of the polygenic risk score for osteoporosis (PRS); the multiplicative interaction term examined the relationship between creatinine and PRS.ResultsCreatinine showed a U-shaped association with osteoporosis, with a nadir near 80 μmol/L (overall P<0.001; nonlinearity P<0.001). In piecewise models, each 1-μmol/L increase corresponded to a 2.0% lower osteoporosis risk within 25–80 μmol/L (HR = 0.980, 95% CI 0.978–0.982) and a 1.1% higher risk within 80–130 μmol/L (HR = 1.011, 95% CI 1.006–1.017). For fractures, the dose–response was J-shaped around the same nadir: risk decreased by 1.0% per μmol in 25–80 μmol/L (HR = 0.990, 95% CI 0.988–0.992) and increased by 0.3% per μmol in 80–130 μmol/L (HR = 1.003, 95% CI 0.999–1.006). Sex-stratified patterns were directionally concordant. In PRS-stratified categorical analyses (vs G4), the low-creatinine stratum (G1) carried higher osteoporosis risk across tertiles (HRs 1.925, 1.811, and 1.592 for low, intermediate, and high PRS). Creatinine×PRS interactions were not significant (osteoporosis P = 0.132; fractures P = 0.210).ConclusionsBaseline serum creatinine was significantly and nonlinearly associated with incident osteoporosis (U-shaped pattern) and fractures (J-shaped pattern), with the lowest risk observed at approximately 80 μmol/L, and there was a notable sex difference (higher in males). These associations were independent of genetic susceptibility, suggesting that serum creatinine may serve as a low-cost adjunct marker for clinical risk stratification and surveillance of osteoporosis.